Identity formation and community solidarity : second temple historiographies in discourse with (South) African theologies of reconstruction - Cezula, Ntozakhe Simon (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.